THE INFLUENCE ANALYSIS OF REWARDS, WORK-LIFE BALANCE AND CAREER DEVELOPMENT IN INFLUENCING EMPLOYEE RETENTION THROUGH JOB SATISFACTION AND EMPLOYEE WELL-BEING IN THE MANUFACTURING INDUSTRY IN CIKARANG - Simbolon, Jeff Aditya; Tanuwijaya, Justine; Gunawan, Andreas Wahyu (International Journal of Social Service and Research, 2024)
This study aims to explore the role of reward, work-life balance, career development, job satisfaction, and employee well-being in influencing employee retention. The research was quantitative and collected data cross-sectionally from the Manufacturing Industry sector in the Cikarang area in 2024. The study will examine independent variables, including Reward, Work-life Balance, and Career Development, and their impact on dependent variables such as Job Satisfaction, Employee Well-being, and Employee Retention. The results of the hypothesis test show that the better the reward received by operator employees, the better it has a good influence on Job Satissefaction. The better the Career Development owned by the operator employees in the manufacturing industry, the more it improves the welfare of the operator's employees. It is concluded that if employees have opportunities for career development at the company where they work, it will increase the level of job satisfaction.